The Association Knowledge and Community Practice with the Incidence of DHF (Study in the Village of Putat Jaya Surabaya on 2010-2014) - Rahmawati Sari Budi Utami (Universitas Airlangga, 2015)
Dengue Hemorrhagic Fever (DHF) is still one of problems today in Indonesia. Incident Rate (IR) and Case Fatality Rate (CFR) is DHF incidence indicator. The objective of the research was to identify and analyze relationship between knowledge and communitypractice with dengue incidence in the Village Putat Jaya Surabaya 2010-2014. This study used a cross-sectional study. Interviews were conducted on 397 people in Village Putat Jaya Surabaya with each proportion 8 people in RW 1, 62 people in RW 2, 35 people in RW 3, 29 people in RW 4, 24 people in RW 5, 12 people in RW 6, 16 people in RW 7, 59 people in RW 8, 23 people in RW 9, 12 people in RW 10, 16 people in RW 11, 22 people in RW 12, 25 people in RW 13, 50 people in RW 14 and 4 people in RW 15. Subjects were selected by simple random sampling. The dependent variable is incidence of DHF. The independent variablesare knowledge and community practice. Data analysis using Chi-Square test with significancy level at 95%. The results showed that there was no relationship between knowledge society (p = 0.206) with dengue's incidence.Practice (p = 0.009) had a association with dengue's incidence. Conclusion of study is practice have a significant relationship with DHF occurrence. Health ministry is recommended to work together across sectors between related stakeholder, dissemination of dengue through electronic media, training of bumantik cadres regularly, increasing community participation through PSN DBD and distribute free mosquito repellent to public. Keywords: knowledge, community practice, incidence of DHF, IR & CFR, community participation